Implementasi Lampu Peringatan Pada Perlintasan Tanpa Palang Pintu Kereta Api Berbasis Mikrokontroler - Aad Hariyadi; Moh. Syakur Romadhoni; M. Abdullah Anshori; Amalia Eka Rakhmania (Journal of Applied Smart Electrical Network and Systems, 2021)
This research aims to make a warning light with a microcontroller base as a control system. With the aim of reducing the use of manual systems in general that are in use today. The advantage of this warning light control system is that it functions to reduce the number of accidents that occur and can be used for railroad crossings where there are still no latches that have not been installed on the railroad railroad crossing (wild road). The display of the work system that is made will be monitored using a web monitoring display that supports and is easy to understand. Even though it has some delay in the process, the planned system has run well based on the average delay value. The experimental results show the average delay measured in the system is 0.31 seconds before sending from the node and 0.49 seconds when there is a change in conditions, while when there is data transmission from the node. The measured packet loss on the system is 0% before transmission and fans and 8.88% when data is transmitted from the node.